Feature-preserving T-mesh construction using skeleton-based polycubes. (January 2015) - Liu, Lei; Zhang, Yongjie; Liu, Yang; Wang, Wenping
Abstract: This paper presents a novel algorithm which uses skeleton-based polycube generation to construct feature-preserving T-meshes. From the skeleton of the input model, we first construct initial cubes in the interior. By projecting corners of interior cubes onto the surface and generating a new layer of boundary cubes, we split the entire interior domain into different cubic regions. With the splitting result, we perform octree subdivision to obtain T-spline control mesh or T-mesh. Surface features are classified into three groups: open curves, closed curves and singularity features. For features without introducing new singularities like open or closed curves, we preserve them by aligning to the parametric lines during subdivision, performing volumetric parameterization from frame field, or modifying the skeleton. For features introducing new singularities, we design templates to handle them. With a valid T-mesh, we calculate rational trivariate T-splines and extract Bézier elements for isogeometric analysis. Highlights: We present a novel algorithm which uses skeleton-based polycube generation to construct T-meshes. Three kinds of features are preserved: open curves, closed curves, singularity features. With a valid T-mesh, we calculate trivariate T-splines for isogeometric analysis.